Knowledge and practices among male medical students regarding smoking and its hazards - Mehmood, Asif; Sarwar, Usman; Ahmed, Waqar; Tahir, Hassan (International Journal of Research in Medical Sciences, 2017)
Background: Tobacco use is the leading preventable cause of death worldwide, and according to the latest estimates, by year 2030, 10 million annual tobacco-attributable deaths worldwide, 70% of which will be in low-middle-income countries. The purpose of study was too assess the knowledge and practices regarding cigarette smoking among male medical students in Allama Iqbal Medical College, Lahore, Pakistan and to assess the awareness of students regarding smoking related health hazards. Methods: A Cross-Sectional Study was conducted From May 2009 - September 2009 in Allama Iqbal Medical College, Lahore, Pakistan. The male students enrolled in Allama Iqbal Medical College Lahore, were selected by non-probability convenient sampling. Results: In present study 47.3% respondents were smokers, 94.1% were knowledgeable about hazards of smoking, 85.9% were aware about passive smoking, and 19.1% started consuming tobacco below 17 years of age. Only 19.1% tried to quit smoking but none of them succeeded. 25% have no family association of smoking. There were 18.2% who’s mostly close friends were smokers only 13.2% smokes more than 15 cigarettes daily. 43.6% said they would smoke cigarette if one of their close friends offer them. 30.5% believe cigarette smoking help to relax and 25% want to quit smoking among them 10% want to quit due to its hazards while 5.9% due to family pressure. Conclusions: Present study concluded that high proportion male medical students smoke cigarette. Most of them were unaware about tobacco consumption hazards, and passive smoking.